Stress in small businessmen from Barranquille in the framework of virtual econo¬mic activity due to confinement in Colombia - Cárdenas Ortiz, Luis Carlos (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This research focuses on knowing the levels of stress in small entrepreneurs from Barranquilla in the framework of virtual economic activity due to the confinement in Colombia, under an analytical perspective, considering testimonies of entrepreneurs and also, the detection of cases of entrepreneurs. who require psychological attention or a complex assessment, or who may present symptoms of stress.